2003
DOI: 10.3141/1858-13
|View full text |Cite
|
Sign up to set email alerts
|

Structured Public Involvement: Problems and Prospects for Improvement

Abstract: Public involvement in transportation planning and design has a problematic history. Professionals lack access to a coherent, organized method for communicating with the public, and some important principles of public involvement known to community design professionals are still being discovered by transportation professionals. A protocol, structured public involvement (SPI), is proposed. SPI was designed to ensure that public involvement is meaningful to the professional and the public. Principles of SPI are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Unlike other countries, CP in Korean transportation projects was reviewed prior to the 1990s, but most studies have been limited to suggesting policies and their necessity [43][44][45][46]. Previous studies have indicated that some of the keys to the success of CP efforts are the serious and timely treatment and follow-up of citizen input, such as online comments, incoming calls, and emails [47,48]. Therefore, the traditional techniques of CP, such as personal interviews, public meetings or hearings, and telephone techniques, could rarely be successful.…”
Section: Citizen Participation In the Transportation Fieldmentioning
confidence: 99%
“…Unlike other countries, CP in Korean transportation projects was reviewed prior to the 1990s, but most studies have been limited to suggesting policies and their necessity [43][44][45][46]. Previous studies have indicated that some of the keys to the success of CP efforts are the serious and timely treatment and follow-up of citizen input, such as online comments, incoming calls, and emails [47,48]. Therefore, the traditional techniques of CP, such as personal interviews, public meetings or hearings, and telephone techniques, could rarely be successful.…”
Section: Citizen Participation In the Transportation Fieldmentioning
confidence: 99%
“…Studies over the years have suggested the need for tools that help planners and designers be more effective (Bishop 1998, Voss et al 2003. Several reviews exist that describe participatory geospatial information tools designed to combine analysis and deliberation (Balram and Dragacevic 2006, Brail 2008, Grossardt, Bailey and Brumm 2003, Jankowski and Nyerges 2001, Klosterman 1997, and Nyerges, Couclelis and McMaster 2011. Decision support software tends to be developed narrowly because of the complexity of space-time decision problems (Jankowski et al 2006).…”
Section: A Web Platform To Address Geodesign Dynamicsmentioning
confidence: 99%
“…The public can develop useful compromises. These principles form the basis for the KTC's Structured Public Involvement (SPI) protocols [14]. SPI protocols are designed to ensure that public input into the design and planning process happens before the process is begun: that is, planners and/or designers gain a clear and documented image of public preferences as part of their initial design process.…”
Section: Significant Aspects Of Successful Public Involvementmentioning
confidence: 99%